Eco-efficiency of Grinding Processes and Systems - Winter, Marius (Sustainable Production, Life Cycle Engineering and Management, 2016)
This research monograph aims at presenting an integrated assessment approach to describe, model, evaluate and improve the eco-efficiency of existing and new grinding processes and systems. Various combinations of grinding process parameters and system configurations can be evaluated based on the eco-efficiency. The book presents the novel concept of empirical and physical modeling of technological, economic and environmental impact indicators. This includes the integrated evaluation of different grinding process and system scenarios. The book is a valuable read for research experts and practitioners in the field of eco-efficiency of manufacturing processes but the book may also be beneficial for graduate students.